Identification of Customary Delict of South Papua and Its Customary Sanctions as a Form of Preservation of Customary Law - Alputila, Marlyn Jane; Tajuddin, Mulyadi Alrianto; Y. Badilla, Nurul Widhanita (Devotion : Journal of Research and Community Service, 2023)
Until now, there has been no specific reference to customary offenses and customary courts in Papua, especially the South Papua Customary Court, except for the writings of some anthropologists who touch on this issue in discussing the leadership system or community structure or customary government system in Papua. The purpose of this study is to determine the existence or existence of customary law in the Anim Ha customary territory and the need for mapping customary law in force in South Papua by identifying customary violations and customary sanctions. This research uses a descriptive method of analysis with a normative juridical approach supported by empirical data, namely direct data from customary law communities and secondary data, namely legal material such as laws and regulations, legal doctrines, and court decisions/jurisprudence, and supported by primary data, namely by conducting interviews with related parties. There are three types of customary sanctions in South Papua, namely legal action in the form of imposition of fines (objects or goods), legal action in the form of imposing physical and spiritual suffering on violators (physical and psychological punishment), in the form of legal action to restore magical balance (punishment in the form of carrying out traditional ceremonies / rituals). Customary law communities in South Papua in fact although state law applies the principle of legal centralism, customary law is more dominant in regulating community life because it is considered more beneficial to the parties in resolving cases or disputes than positive law.